Deformation-induced ω-phase transformation in a β-type titanium alloy during tensile deformation. (15th March 2017) - Liu, Huihong; Niinomi, Mitsuo; Nakai, Masaaki; Cho, Ken; Fujii, Hidetoshi
Abstract: Deformation-induced ω-phase transformation during tensile deformation was investigated in the developed spinal-support alloy, Ti-9Cr-0.2O. Both preferential single-variant ω transformation along its [0001] direction and growth and/or assembling of uniformly distributed ω particles undergo in the alloy during tensile deformation. It is confirmed that this deformation-induced ω-phase transformation can be triggered by elastic strain or stress without plastic deformation. Furthermore, a re-orientation process works for this transformation; that is, the ω1 variant may re-orientate into the ω2 variant via 001 ⟨110〉 twinning-type mechanism probably related to the external loading condition and the orientations of ω and β phases. Graphical abstract: